Forest natural regeneration and biomass production after slash and burn in a seasonally dry forest in the Southern Brazilian Amazon - d'Oliveira, M. V. N.; Alvarado, E. C.; Santos, J. C.; Carvalho, J. A. [UNESP] (Elsevier B.V., 2011)
This study estimates the aboveground biomass accumulation after forest clearing and slash burning and describes the structure and successional development of the secondary forest in the seasonally dry southern Amazon. The original burn study was conducted in four land clearings in 1997, 1998, and 1999. The size of the clearings varied from 1 to 9 ha. The native forest was felled, allowed to dry for approximately three months and then burned by the end of the dry season. A census was conducted in the central 1-ha forest on each site prior to the area's felling and burn. The aboveground biomass (AGB) and structure were similar to other primary tropical forests. However, the high density of Cecropia spp. before the forest felling and burn treatment indicates past low intensity disturbances. Seven and eight years after the fire, the fallow forests were still in an early successional stage dominated by Cecropia spp. The four areas had a high biomass accumulation during the studied period, varying from 7.5 to 15.0 Mg ha(-1) year(-1). The lower biomass accumulation in one plot was an effect of a higher fire severity, produced by the one-year difference in time between slash and burn of the forest, slowing the natural regeneration of Cecropia spp. The time needed for this forest to recover to the pre-fire AGB levels ranged from 20 to 30 years, assuming the current AGB accumulation rates are maintained. Considering these results, the maintenance of regenerating secondary forests in the Amazon would be a significant contribution to soil and watershed protection, minimizing biodiversity losses and perhaps mitigating climatic changes effects in the region. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Secondary forests regeneration; Tropical forest; Aboveground biomass accumulation; Biomass burning